Neuromodulatory functions exerted by oxytocin on different populations of hippocampal neurons in rodents - Talpo, Francesca; Spaiardi, Paolo; Castagno, Antonio Nicolas; Maniezzi, Claudia; Raffin, Francesca; Terribile, Giulia; Sancini, Giulio; Pisani, Antonio; Biella, Gerardo Rosario (Frontiers in Cellular Neuroscience, 2023)
Oxytocin (OT) is a neuropeptide widely known for its peripheral hormonal effects (i.e. parturition and lactation) and central neuromodulatory functions, related especially to social behavior and social, spatial, and episodic memory. The hippocampus is a key structure for these functions, it is innervated by oxytocinergic fibers, and contains OT receptors (OTRs). The hippocampal OTR distribution is not homogeneous among its subregions and types of neuronal cells, reflecting the specificity of oxytocin’s modulatory action. In this review, we describe the most recent discoveries in OT/OTR signaling in the hippocampus, focusing primarly on the electrophysiological oxytocinergic modulation of the OTR-expressing hippocampal neurons. We then look at the effect this modulation has on the balance of excitation/inhibition and synaptic plasticity in each hippocampal subregion. Additionally, we review OTR downstream signaling, which underlies the OT effects observed in different types of hippocampal neuron. Overall, this review comprehensively summarizes the advancements in unraveling the neuromodulatory functions exerted by OT on specific hippocampal networks.